The short-run economic costs of COVID-19 in developing countries in 2020: A synthesis of results from a multi-country modeling exercise - Pauw, Karl; Smart, Jenny; Thurlow, James (International Food Policy Research Institute, 2021)
As COVID-19 spread across the globe in early 2020, governments had to make difficult choices to balance the socioeconomic costs of social distancing and lockdown measures, on the one hand, and the human costs of increased morbidity and mortality of an unchecked pandemic, on the other. The challenge was particularly daunting for developing countries with their often illequipped and underfunded health systems coupled with general skepticism about the effectiveness of economic restrictions to curb viral spread, especially in densely populated informal urban communities (The Economist 2020). Poorer developing country populations also tend to be less resilient to income shocks, while the social protection measures needed to mitigate against income losses are costly. With developing country governments already heavily indebted before the pandemic (Onyekwena and Ekeruche 2019), and with further anticipated losses in tax revenues due to COVID-related economic restrictions, their ability to finance palliative measures without sacrificing much-needed, longer-term public investments has remained a major concern.